IV International Meeting «Early Events in Human Pathologies» - Galoyan, A.A.; Vassetzky, Y.S. (Вiopolymers and Cell, 2011)
The meeting «Early Events in Human Pathologies» held in Yerevan (Republica of Armenia) on October
12–16, 2011 will unite Armenian, Ukrainian, Russian, and French scientists working on cancer,
neurodegenerative and autoimmune diseases. This is the fourth meeting in this very successful series, the
previous mettings were held in Moscow, Russian Federation (2007), Kiev, Ukraine (2009) and Barbizon,
France (2010).